Imprint of Trace Dissolved Oxygen on Prokaryoplankton Community Structure in an Oxygen Minimum Zone - Medina Faull, Luis; Mara, Paraskevi; Taylor, Gordon T.; Edgcomb, Virginia P. (Frontiers in Marine Science, 2020)
The Eastern Tropical North Pacific (ETNP) is a large, persistent, and intensifying oxygen minimum zone (OMZ) that accounts for almost half of the total area of global OMZs. Within the OMZ core (∼350–700 m depth), dissolved oxygen is typically near or below the analytical detection limit of modern sensors (∼10 nM). Steep oxygen gradients above and below the OMZ core lead to vertical structuring of microbial communities that also vary between particle-associated (PA) and free-living (FL) size fractions. Here, we use 16S amplicon sequencing (iTags) to analyze the diversity and distribution of prokaryotic populations between FL and PA size fractions and among the range of ambient redox conditions. The hydrographic conditions at our study area were distinct from those previously reported in the ETNP and other OMZs, such as the ETSP. Trace oxygen concentrations (∼0.35 μM) were present throughout the OMZ core at our sampling location. Consequently, nitrite accumulations typically reported for OMZ cores were absent as were sequences for anammox bacteria (Brocadiales genus Candidatus Scalindua), which are commonly found across oxic-anoxic boundaries in other systems. However, ammonia-oxidizing bacteria (AOB) and archaea (AOA) distributions and maximal autotrophic carbon assimilation rates (1.4 μM C d–1) coincided with a pronounced ammonium concentration maximum near the top of the OMZ core. In addition, members of the genus Nitrospina, a dominant nitrite-oxidizing bacterial (NOB) clade were present suggesting that both ammonia and nitrite oxidation occur at trace oxygen concentrations. Analysis of similarity test (ANOSIM) and Non-metric Dimensional Scaling (nMDS) revealed that bacterial and archaeal phylogenetic representations were significantly different between size fractions. Based on ANOSIM and iTag profiles, composition of PA assemblages was less influenced by the prevailing depth-dependent biogeochemical regime than the FL fraction. Based on the presence of AOA, NOB and trace oxygen in the OMZ core we suggest that nitrification is an active process in the nitrogen cycle of this region of the ETNP OMZ.